2022
DOI: 10.1002/adem.202101063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Precipitates in Mg−Sm Alloys on Their Deformation Behavior and Yield Asymmetry

Abstract: The strengthening effect of precipitates in a Mg−0.4Sm (wt%) alloy on dislocation slip and extension twinning (ET) is evaluated by experimental work and viscoplastic self‐consistent (VPSC) modeling. Experimental results reveal that the extruded Mg−Sm alloy consists of rare‐earth texture (<−12−11> // ED) and extrusion texture (<−12−10> // ED) components. After aging precipitation, tensile yield stress is more effectively enhanced than compressive yield stress. Transmission electron microscopy (TEM) analysis con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…However, a phenomenon is often observed that some materials have different flow stresses between tension and compression, and it is defined as the strength differential effect or asymmetric yielding. [15][16][17] Concerning the constitutive modeling of the different metals and alloys, most attention has been devoted to the asymmetric yielding and hardening type. [18,19] Stoughton and Yoon [20] described the strength differential effect of sheet metal forming The TB9 titanium alloy is one of the most promising materials for engineering application due to high strength, high toughness, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, a phenomenon is often observed that some materials have different flow stresses between tension and compression, and it is defined as the strength differential effect or asymmetric yielding. [15][16][17] Concerning the constitutive modeling of the different metals and alloys, most attention has been devoted to the asymmetric yielding and hardening type. [18,19] Stoughton and Yoon [20] described the strength differential effect of sheet metal forming The TB9 titanium alloy is one of the most promising materials for engineering application due to high strength, high toughness, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%